2011
DOI: 10.1038/ncomms1541
|View full text |Cite
|
Sign up to set email alerts
|

Direct stereoselective α-arylation of unmodified enals using an organocatalytic cross-coupling-like reaction

Abstract: Cross-coupling reactions typically rely on the use of transition metal catalysis. However, although achieving this process using metal-free organocatalysts is highly challenging, it could offer unique opportunities to discover novel bond-forming strategies in organic synthesis. Here we report a new amine catalysed direct stereoselective C-H α -arylation reaction of unmodifi ed enals with bromoarenes. The power of this process, which involves an unprecedented iminiumMichael-alkylation-enamine-retro-Michael casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Transition-metal-free arylations Song et al [40] subsequently reported the direct stereo-selective a-arylation of enals via TMF conditions. After an intensive investigation, they provided a simple and efficient protocol showing simple, easy and metal-free synthesis of arylated products via organo-catalyst mediation (Scheme 21).…”
Section: Scheme 15 Synthesis Of Oxoindole Derivatives Via Tbhp (Oxidant)mentioning
confidence: 98%
“…Transition-metal-free arylations Song et al [40] subsequently reported the direct stereo-selective a-arylation of enals via TMF conditions. After an intensive investigation, they provided a simple and efficient protocol showing simple, easy and metal-free synthesis of arylated products via organo-catalyst mediation (Scheme 21).…”
Section: Scheme 15 Synthesis Of Oxoindole Derivatives Via Tbhp (Oxidant)mentioning
confidence: 98%
“…On the basis of the above resultsa nd our previous study on the organocatalytic coupling of prefunctionalized para-bromophenols and enals through Michael addition/dearomatization/ cyclopropanation/enamination/ retro-Michael cascade process, [15] we proposed as imilarc atalytic cycle for the process. The pathway involves an in situ bromination-Friedel-Crafts alkylation dearomatization/cyclopropanation/enamination/retro-Michael (ring opening) cascade sequence (Scheme 3).…”
mentioning
confidence: 79%
“…By considering the lack of organocatalytic methods for parafunctionalization of 1-naphthols, and inspired by our earlier study of organocatalytic coupling of prefunctionalized parabromophenols and enals through aM ichael addition/S N 2-substitution/retro-Michael cascade sequence (Scheme 2), [15] we envisioned that prefunctionalized 4-bromo-1-naphthols might direct the installation of the enals into the para-position of the structures. However,w ef ound that the process presents daunting challenges in our exploratory investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we developed an organocatalytic stereoselective cross-coupling-like a-arylation reaction of aromatic a,b-unsaturated aldehydes with 4-bromophenols and 3-bromoindoles (Scheme 1 a). [7] However, when an aliphatic crotonaldehyde was subjected to the reaction conditions, an unexpected 4-methyl benzaldehyde was obtained (Scheme 1 b). This serendipitous discovery prompted us to investigate this interesting "side reaction".…”
mentioning
confidence: 99%